Hopeless practical deliberation – reply to Bobier. (23rd June 2019) - Mueller, Andy
Abstract: Bobier (2017) argued that hope is necessary for practical deliberation. I will demonstrate that Bobier's argument for this thesis fails. The problem is that one of its main premisses rests on a sufficient condition for hoping that is subject to counterexamples. I consider two ways to save the argument, but show that they are unsuccessful in doing so.